Consumers' confidence towards halal logo products among the muslims of UTM and Johor Bahru - Nur Dianah Ibrahim, 1993-; Indra Sukati 638113; Fakulti Pengurusan 538641 (2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016